TOWARDS SUSTAINABILITY: THE INNOVATION PATHS OF SOCIAL ENTERPRISE. (21st April 2017) - PICCIOTTI, Antonio
ABSTRACT: The concepts of sustainable development and social economy are currently undergoing a process of convergence, determined by the extension of the concept of sustainability and the role of social enterprise. In a context in which the primary focus of management literature, especially of North American origin, concerns the concept and practices of social entrepreneurship, this paper explores the experiences of European social enterprises and in particular of Italian social cooperatives. Social cooperatives are experimenting with initiatives capable of responding to the emergence of new needs and changes in society in a sustainable way. Based on an analysis of the experience of various social cooperatives operating in the field of renewable energy sources, tourism, and the use of assets confiscated from the Mafia, this paper aims to highlight how social enterprise manages to create contexts of sustainable development, thereby building interorganizational and intersectoral collaborative networks aimed at the activation of new paths for local development. This represents evidence of the specific nature of the social enterprise, which is able to establish a number of coordination mechanisms. It creates new businesses with public and private, and profit and non‐profit partners, with the aim of achieving a stated goal, or enters into contractual arrangements, in order to establish business partnerships and build entire local manufacturing supply chains. In this way social enterprise promotes interaction between resources of a public, market and community nature.